Erotic grotesque nonsense : the mass culture of Japanese modern times - Silverberg, Miriam Rom, 1951-2008 (Asia Pacific modern, 2006)
Employing the concept of montage as a metaphor that informed the organization of Japanese mass culture during the 1920s and 1930s, this work challenges the erasure of Japanese colonialism and its legacies.